Existing buffalo husbandry practices at household farming level in selected coastal regions of Bangladesh (Asian Journal of Medical and Biological Research, 2020)
The study was attempted to collect information on buffalo husbandry practices existing in household farming level along with farmers’ status and problems they faced with probable solutions in selected coastal regions of Bangladesh. Data were collected from eighty (80) randomly interviewed household farmers of two coastal districts (Bhola and Patuakhali) through questionnaire from 1st January to 30th June 2019. Buffalo rearing was practiced by male farmers (85%) in age group of 31-45 yrs (47.5%) having primary level education (51.25%) and belonged to small category of farmers (52.5%) whose main occupation is agriculture (76.25%). About 82.5% farmers used own capital while 96.25% farmers practiced buffalo rearing without any training. Majority (80%) of the farmers had small herd size (